A gadget for blind people to use in daily activities - Arbaiyah Abdul Ghaffar (School of Electrical System Engineering, University Malaysia Perlis, 2011)
This project discusses the design of an Ultrasonic Blind Stick that creating to help blind people to walk and do their activities easier. This stick use battery 9V as voltage supply and ultrasonic sensor to detect things around blind people with a range about 2cm to 1m. The distance of any obstacle is measured through ultrasonic waves which can easily understand the blind people that how far they are.